Proceeding International seminar : Education transformation toward excellent quality based on ASEAN community characteristics - Proceeding_International_seminar_:_Education_transformation_toward_excellent_quality_based_on_ASEAN (Fak. Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2014)
et,1/irh,c.1